DSP BASED MEASURING LINE-SCAN CCD CAMERA - Fischer, Jan; Radil, Tomas (International Journal of Computing, 2014)
A simple, flexible and programmable line-scan CCD camera is presented in this paper. This camera is designed for measurement purposes such as dimension and position measurements. Camera enables implementation of various signal-processing algorithms as well as usage of various types of CCD sensors.